2016
DOI: 10.1002/mar.20847
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration and Investigation of Edible Insect Consumption: The Impacts of Image and Description on Risk Perceptions and Purchase Intent

Abstract: As a result of the dramatic increase in global population, food waste, and unsustainable practices, the United Nations urges the promotion of edible insects as an alternative food source. However, edible insects are perceived as an unappealing, disgusting food source despite the nutritional and sustainable advantages, especially among Westerners. Therefore, research is needed to bridge the gap between the call for examining alternative food sources and the marketing initiatives to improve purchasing behavior. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
149
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 128 publications
(154 citation statements)
references
References 87 publications
3
149
0
2
Order By: Relevance
“…'s () study. Expected liking was measured with two items and purchase intention was measured with four items that were adapted from Baker et al .’s () study. All measurement items were measured on a 7‐point Likert‐type scale that was anchored between (1) Strongly disagree and (7) Strongly agree.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…'s () study. Expected liking was measured with two items and purchase intention was measured with four items that were adapted from Baker et al .’s () study. All measurement items were measured on a 7‐point Likert‐type scale that was anchored between (1) Strongly disagree and (7) Strongly agree.…”
Section: Methodsmentioning
confidence: 99%
“…However, adopting edible insects for human consumption faces several barriers due to the negative perceptions associated with insects such as disgust (Baker et al . ). Some research indicates that information processing is the key to combat against such negative perceptions of edible insect (Baker et al .…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 97%
See 2 more Smart Citations
“…2014; Looy et al ; Baker et al ). However, although it was found that edible insects should be powdered and then used as a food ingredient in order to minimize the consumers' risk perceptions (Baker et al ), there are significant literature gaps in terms of the commercialization of edible insect powder. In other words, previous literature does not provide a holistic approach to the commercialization of edible insects.…”
Section: Introductionmentioning
confidence: 99%